Integration of Local Wisdom in Digital Learning: A Literature Review - Jusriadi Jusriadi; Muhammad Abdullah; Istiqamah Istiqamah; Muthiah Prasong (Jurnal Edukasi Terkini, 2025)
Purpose-This literature review aims to explore the integration of local wisdom into digital learning to enhance educational relevance and effectiveness. Research Methodology/Design/Approach-Using bibliometric analysis with VOSviewer, the study maps key research themes, connections, and trends within this emerging field. The approach focuses on analyzing patterns in keywords related to students, teachers, digital tools, and learning models informed by local cultural knowledge. Finding-Findings reveal that integrating local wisdom enriches digital learning by fostering culturally responsive pedagogy that supports student identity and character development. Innovative media such as digital comics are highlighted as effective tools in this context. Originality / Value-The review also identifies growing research interest, particularly from Indonesia, emphasizing the importance of adaptive, data-driven learning models based on local contexts. The study provides valuable insights for educators and policymakers seeking to develop inclusive and relevant digital learning frameworks grounded in local knowledge.